The Effect of Complexity and Work Motivation on The Performance of Minor Change-Scale Product Development Projects In Automotive Manufacturing Industry - Annisa Dewi Akbari; Indah Sepwina Putri (OPSI, 2021)
The increasing market competition in the Indonesian automotive manufacturing industry requires automotive manufacturing companies to adapt to changes through product development activities. Unfortunately, failure in product development projects is still high. One of the possible key factors of a successful product development project is work motivation. Another factor that is suspected to affect is the complexity of the project. Therefore, this study aims to find the effect of work motivation and project complexity on product development project performance. The research was conducted on 94 members of product development project team in Indonesian automotive manufacturing industry with a minor change scale using purposive sampling. Data was collected through online questionnaire with a response rate of 65.7% and then analyzed using PLS-SEM. The results of the study showed that project complexity had a positive effect on work motivation and otherwise on project performance. On the other hand, it turns out that work motivation is not proven to affect the performance of product development projects in the automotive manufacturing industry in Indonesia.